ApoE plasma levels and risk of cardiovascular mortality in old age. - Simon P Mooijaart (Public Library of Science (PLoS), 2006)
Background The epsilon2, epsilon3, and epsilon4 alleles of the apolipoprotein E gene (APOE) encode three isoforms, apoE2, E3, and E4, respectively. The apoE isoforms circulate in different plasma concentrations, but plasma concentrations of the same isoform also differ between individuals. Whereas the isoforms have been associated with cardiovascular disease, the relation between plasma apoE levels and cardiovascular disease is unknown. Methods and findings We assessed APOE genotypes, plasma levels of apoE, cardiovascular risk factors, and mortality in a population-based sample of 546 individuals aged 85 y who participated in the Leiden 85-plus Study and were prospectively followed for specific causes of death for 5 y. Participants in the highest tertile of apoE levels suffered a twofold-increased risk of cardiovascular mortality (hazard ratio compared to lowest tertile, 2.08; 95% confidence interval [CI], 1.30 to 3.33). Among the 324 participants with the epsilon3epsilon3 genotype, the hazard from cardiovascular disease was threefold increased (highest versus lowest tertile 3.01; 95% CI 1.60 to 5.66), with similar estimates for men and women. Other causes of death were not increased significantly. Plasma levels of apoE in epsilon3epsilon3 participants were positively correlated with total cholesterol (p < 0.001), low-density lipoprotein cholesterol (p < 0.001) and triglycerides (p < 0.001) and negatively with high-density lipoprotein cholesterol levels (p = 0.010). Adjustment for plasma lipids did not change the hazard ratios, whereas interaction was absent. The risk associated with high levels of apoE, however, was strongest in participants from the lowest tertile of C-reactive protein (CRP) levels and absent in those from the highest tertile (p(interaction) < 0.001). Among participants from the lowest tertile of CRP levels, those with a high apoE levels had a significantly steeper increase in CRP than those with low apoE levels (p = 0.020). Similar cardiovascular mortality risks as in epsilon3epsilon3 participants were found in epsilon2 and epsilon4 carriers. Conclusions In old age, high plasma apoE levels precede an increase of circulating CRP and strongly associates with cardiovascular mortality, independent of APOE genotype and plasma lipids.